Identification of Enterococcus Species Isolated from Commercial Fish Feeds and Infected Fish Specimens - Kumru, S; Dengiz Balta, Z; Aliu, H; Balta, F (Hellenic Veterinary Medical Society / Ελληνική Κτηνιατρική Εταιρεία, 2024)
Enterococcus is a Gram‐positive cocci bacterium that can survive in different environmental conditions such as water, plant, and soil. They are also bacteriological signs of fecal contamination. In aquaculture facilities, Enterococcus species have appeared as one of the crucial opportunistic fish pathogens. Enterococcus-caused fish diseases have been reported in different fish species like yellow tail, turbot, and tilapia. Even though Enterococcus species are used as probiotics and are members of the gastrointestinal flora, they can cause pathogenicity like sepsis, wound infections, urinary tract infections, and others. In this study, we isolated bacterial samples from diseased rainbow trout and trout feed. Based on the API 20 strep test kit, they were determined as Enterococcus faecium. While fish isolate samples had 74.4%-99.9% similarity to E. faecium, trout feed isolate samples had 96.4%-99.9% similarity to E. faecium. Moreover, PCR was performed from trout feed isolate samples by using the universal 16S rRNA primers. Sequence results indicate that the samples were E. faecium and E. faecalis. The phylogenetic tree was constructed with other Enterococcus species of 16S rRNA and our samples were located in the E. faecium and E. faecalis species. In conclusion, there may be contamination of Enterococcus with food or other factors. They are opportunistic microorganisms and cause pathogenicity when the host immunity weakens. This may be the first report of Enterococcus contamination and pathogenicity on feeds and fish. Even though all samples with API 20 strep test kit were identified as E. faecium, they had the lower percentage similarity, so they may be E. faecalis and other Enterococcus species. Thus, further studies are needed to understand their probiotic and pathogenicity functions in aquaculture production.